From Monitoring to Understanding: AIOps for Dynamic Infrastructure - Allam, Hitesh (International Journal of AI, BigData, Computational and Management Studies, 2023)
The need to overcome these traditional infrastructure monitoring has become even more pressing as IT systems grow ever more complex. Modern dynamic, cloud-native, and hybrid systems generate more enormous volumes of too complicated and fast information for human oversight. This article investigates the shift from conventional monitoring tools centered on their metrics, logs, and thresholds to the application of Artificial Intelligence for IT Operations (AIOps), which permits not just monitoring but also a deep understanding of these system behavior. Using ML, natural language processing, and advanced anomaly detection, AIOps independently correlates occurrences, finds fundamental causes, and forecasts future problems before more operational interruptions. This shift represents a basic transformation from reactive event management to proactive and predictive activities. The article defines the basic technologies supporting AIOps and investigates their integration into present IT systems to raise these observability and the decision-making accuracy. It also looks at how AIOps handles important challenges including data silos, alert fatigue, and rule-based monitoring of these limitations. Emphasizing tangible benefits including reduced downtime and accelerated incident resolution, a case study shows the actual deployment of AIOps in an actual world hybrid infrastructure. In the end, we look at the huge effects of using AIOps, seeing it not only as a technology improvement but also as a cultural revolution toward more intelligent, autonomous IT operations. As companies grow their digital ecosystems, the conclusion emphasizes the growing strategic relevance of AIOps and projects its future importance